2017
DOI: 10.18632/oncotarget.20831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol consumption, cigarette smoking, and betel quid chewing on upper digestive diseases: a large cross-sectional study and meta-analysis

Abstract: Cigarette smoking is a well-known risk factor of upper digestive diseases. Findings on alcohol's effect on these diseases are inconsistent and with the exception of its association with esophageal cancer, little is known about betel quid chewing. This study investigated the association between use of these three substances and upper digestive diseases. We collected data from 9,275 patients receiving upper endoscopies between April 2008 and December 2013. Polynomial regressions were used to analyze the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 53 publications
3
21
0
2
Order By: Relevance
“…The risk intensity of substances used may be slightly fluctuated, depending on different indicators such as age at start, daily average, and cumulative amount were applied. Previous population and laboratory studies have found that cumulative consumption of alcohol, cigarette, or areca nut, the common substances used in Asia countries, have largely contributed to the development of different upper digestive diseases . The similar findings of this study suggested the validity of this study design.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The risk intensity of substances used may be slightly fluctuated, depending on different indicators such as age at start, daily average, and cumulative amount were applied. Previous population and laboratory studies have found that cumulative consumption of alcohol, cigarette, or areca nut, the common substances used in Asia countries, have largely contributed to the development of different upper digestive diseases . The similar findings of this study suggested the validity of this study design.…”
Section: Discussionsupporting
confidence: 85%
“…Second, substance dosage were collected by questionnaire, so there may be some recall bias, though questionnaire was designed and interviewer was trained to reduce this bias. In addition, our previous studies have validated the good quality of information about those three substances used . Third, we had fewer ESCC patients; thus, the results of further analysis such as dose‐response of substance exposure and ESCC risk might fluctuate and were less reliable than our previous case‐control studies .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations